Progress in research and technological advancements of commercial concentrated solar thermal power plants - Imran Khan, Muhammad; Asfand, Faisal; Al-Ghamdi, Sami G. (Solar energy, 2023)
A global transition towards more sustainable production and consumption systems is underway. This transition process is particularly visible in energy systems, where modern renewables, majorly solar PV and wind power, accounted for around 10 % of global power production in 2020. It is widely believed that the transition to a low carbon economy would inevitably increase energy storage requirement to a significant extent in the near future. In this context, concentrated solar power (CSP) technologies are seen to be one of the most promising ways to generate electric power in coming decades. To reduce the cost of power generation from CSP technologies, over 1000 articles have been published in the last five years, and it is necessary to observe the overall research and technological advancements in this sector which is missing in the current literature. To bridge this gap, this work presents a comprehensive review on the actual state of all major components of cutting-edge CSP technologies and condenses all the available information and categorizes them considering the main functional parts and remarking the current research progress in each part as well as the future challenging issues. It intends to understand and explain the foundations of the innovative concepts, future research directions and strategies developed over the past 10 years to tune the engineering and thermal sciences of concentrated solar power. It is evident that the cost has come down, however to make the cost of CSP technology at par with other renewable power sources, there are multiple challenges especially in water consumption, materials design, and receiver subsystems. Each of these challenges is discussed in detail and suggestions are presented for addressing the challenges. The information and insights presented in this detailed review study is expected to serve as a good resource for practicing engineers and researchers intending to undertake their research on this subject.